2006
DOI: 10.1002/gps.1446
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy and safety of olanzapine and risperidone in the treatment of elderly patients with schizophrenia: an open study of six months duration

Abstract: Both drugs were well tolerated and their use was associated with fewer symptoms of schizophrenia and less adverse effects than were seen when the patients were taking a typical antipsychotic at baseline. Olanzapine appears to have particular benefit with regard to quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…The process was monitored and was of variable length (Ritchie et al, 2003). Phase C was the assessment period of the 6-months following completion of switching (Ritchie et al, 2006) and Period D was a further 3 year follow up of this study population. This paper describes adherence to therapy throughout periods B, C and D. The mean duration of Phase B was 28 days, therefore, the total duration of follow up of patients from the date of switching to risperidone or olanzapine was approximately 186 weeks, or just over 3½ years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process was monitored and was of variable length (Ritchie et al, 2003). Phase C was the assessment period of the 6-months following completion of switching (Ritchie et al, 2006) and Period D was a further 3 year follow up of this study population. This paper describes adherence to therapy throughout periods B, C and D. The mean duration of Phase B was 28 days, therefore, the total duration of follow up of patients from the date of switching to risperidone or olanzapine was approximately 186 weeks, or just over 3½ years.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence that does exist though suggests that atypical antipsychotics may be of particular benefit in managing this patient group (Ritchie, 2005). We have reported that both olanzapine and risperidone demonstrated improved effectiveness for up to 6 months following a switch from conventional antipsychotics (Ritchie et al, 2003;Ritchie et al, 2006). Continued effectiveness after this intensive, acute switch will be affected by on-going, longterm adherence to these new drugs and it has been argued that longer term adherence is a good proxy measure for a global index of antipsychotic effectiveness (Lieberman et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Adverse outcomes potentially attributable to these drugs, such as hypotension, acute urinary retention, and rhabdomyolysis, are known to cause this injury [6]. Moreover, pneumonia, acute myocardial infarction, and ventricular arrhythmia have been associated with these drugs in former population-based studies and renal damage may also co-occur with these events [7].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, apela-se à precaução e avaliação de riscos-benefícios para a sua utilização. Outros estudos revelam, na sequência da substituição de antipsicóticos típicos por atípicos e na sequência de períodos de acompanhamento para avaliação dos resultados, vantagens da utilização de antipsicóticos atípicos tais como menos efeitos colaterais e melhor qualidade de vida (Finkel, et al, 2009;Ritchie, et al, 2006).…”
Section: Discussionunclassified